Development of a validated Chinese version of the inflammatory bowel disease disability index. Issue 1 (8th January 2020) - Zhang, Jing Jing; Lou, Dan Na; Ma, Han; Yu, Chao Hui; Chen, Li Hua; Li, You Ming
Abstract : Objective: The inflammatory bowel disease disability index (IBD‐DI) has been used to evaluate functional status for patients with inflammatory bowel diseases (IBD). The study aimed to develop a reliable Chinese version of IBD‐DI (C‐IBD‐DI). Methods: Consecutive patients with IBD and healthy controls were recruited from June 2016 to July 2017 in the First Affiliated Hospital, College of Medicine, Zhejiang University (Hangzhou, Zhejiang Province, China) to complete an inflammatory bowel disease questionnaire‐32 (IBDQ‐32), Hamilton's anxiety rating scale (HAMA) and Hamilton's depression rating scale‐24 items (HAMD‐24). The validation process included item reduction, reliability and validity tests. Results: Altogether 122 patients with IBD completed the validation process. Factor analysis reduced the C‐IBD‐DI to 13 items. Cronbach's α coefficient was 0.90. The C‐IBD‐DI scores were correlated with IBDQ‐32 score ( r = −0.79, P  < 0.001), HAMA ( r = 0.78, P  < 0.001) and HAMD‐24 ( r = 0.81, P  < 0.001). The total score of C‐IBD‐DI was significantly higher in patients with active IBD than in those in remission. The intraclass correlation coefficient was 0.83 in the stable IBD group, representing a good test–retest reliability. Those with improved disease activity had a significantly lower C‐IBD‐DI score at the follow‐up visit than at baseline. Patients with IBD had worse disability levels and quality of life than the controls, and were more likely to be anxious and depressed, especially those with active IBD. Conclusions: The validated C‐IBD‐DI comprising 13 questions has highly acceptable reliability and validity. Multicenter studies including large sample sizes are needed to further confirm our results.